The VNTR of the AS3MT gene is associated with brain activations during a memory span task and their training-induced plasticity - Zhao, Wan; Zhang, Qiumei; Chen, Xiongying; Li, Yang; Li, Xiaohong; Du, Boqi; Deng, Xiaoxiang; Ji, Feng; Wang, Chuanyue; Xiang, Yu-Tao; Dong, Qi; Chen, Chuansheng; et al. (Psychological medicine, 2021)
The Arsenic (+3 oxidation state) methyltransferase (AS3MT) gene has been identified as a top risk gene for schizophrenia in several large-scale genome-wide association studies. A variable number tandem repeat (VNTR) of this gene is the most significant expression quantitative trait locus, but its role in brain activity in vivo is still unknown. We first performed a functional magnetic resonance imaging (fMRI) scan of 101 healthy subjects during a memory span task, trained all subjects on an adaptive memory span task for 1 month, and finally performed another fMRI scan after the training. After excluding subjects with excessive head movements for one or more scanning sessions, data from 93 subjects were included in the final analyses. The VNTR was significantly associated with both baseline brain activation and training-induced changes in multiple regions including the prefrontal cortex and the anterior and posterior cingulate cortex. Additionally, it was associated with baseline brain activation in the striatum and the parietal cortex. All these results were corrected based on the family-wise error rate method across the whole brain at the peak level. This study sheds light on the role of AS3MT gene variants in neural plasticity related to memory span training.